Phosphorylation of Bok at Ser-8 blocks its ability to suppress IP3R-mediated calcium mobilization - Caden G. Bonzerato; Katherine R. Keller; Richard J. H. Wojcikiewicz (Cell Communication and Signaling)
Abstract Background Bok is a poorly characterized Bcl-2 protein family member with roles yet to be clearly defined. It is clear, however, that Bok binds strongly to inositol 1,4,5-trisphosphate (IP3) receptors (IP3Rs), which govern the mobilization of Ca2+ from the endoplasmic reticulum, a signaling pathway required for many cellular processes. Also known is that Bok has a highly conserved phosphorylation site for cAMP-dependent protein kinase at serine-8 (Ser-8). Whether Bok, or phosphorylated Bok, has any direct impact on the Ca2+ mobilizing function of IP3Rs remains to be established. Methods Bok Ser-8 phosphorylation was characterized using purified proteins, G-protein coupled receptor agonists that increase cAMP levels in intact cells, mass spectrometry, and immunoreactivity changes. Also, using mammalian cells that exclusively or predominately express IP3R1, to which Bok binds strongly, and a fluorescent Ca2+-sensitive dye or a genetically-encoded Ca2+ sensor, we explored how endogenous and exogenous Bok controls the Ca2+ mobilizing function of IP3R1, and whether Bok phosphorylation at Ser-8, or replacement of Ser-8 with a phosphomimetic amino acid, is regulatory. Results Our results confirm that Ser-8 of Bok is phosphorylated by cAMP-dependent protein kinase, and remarkably that phosphorylation can be detected with Bok specific antibodies. Also, we find that Bok has suppressive effects on IP3R-mediated Ca2+ mobilization in a variety of cell types. Specifically, Bok accelerated the post-maximal decline in G-protein coupled receptor-induced cytosolic Ca2+ concentration, via a mechanism that involves suppression of IP3R-dependent Ca2+ release from the endoplasmic reticulum. These effects were dependent on the Bok-IP3R interaction, as they are only seen with IP3Rs that can bind Bok (e.g., IP3R1). Surprisingly, Bok phosphorylation at Ser-8 weakened the interaction between Bok and IP3R1 and reversed the ability of Bok to suppress IP3R1-mediated Ca2+ mobilization. Conclusions For the first time, Bok was shown to directly suppress IP3R1 activity, which was reversed by Ser-8 phosphorylation. We hypothesize that this suppression of IP3R1 activity is due to Bok regulation of the conformational changes in IP3R1 that mediate channel opening. This study provides new insights on the role of Bok, its interaction with IP3Rs, and the impact it has on IP3R-mediated Ca2+ mobilization.